5x + (3y-x) + (10-2y) = 5x + 3y - x + 10 -2y = 5x - x + 3y - 2y + 10 = 4x + y +10
2x + 3y - x + 5y combine the like terms 2x - x + 3y +5y simple arithmetic x + 8y
3xy + 3y2 = 3y (x + y)
The solution of 4x plus 3y -9 and x -3 is; 5x+3y-3.
x2 + 8xy + 15y2 = (x + 3y) (x + 5y)
-x+3y+6x-6y=5x-3y
It's 5hx+10kx6y.
5x+3y
(a + x - 3y)(a - x + 3y)
5x + (3y-x) + (10-2y) = 5x + 3y - x + 10 -2y = 5x - x + 3y - 2y + 10 = 4x + y +10
2x + 3y - x + 5y combine the like terms 2x - x + 3y +5y simple arithmetic x + 8y
3xy + 3y2 = 3y (x + y)
The solution of 4x plus 3y -9 and x -3 is; 5x+3y-3.
The expression 3x + 3y is a linear combination of two variables, x and y, with coefficients 3. The answer to this expression depends on the specific values of x and y. If x = 2 and y = 4, then the answer would be 3(2) + 3(4) = 6 + 12 = 18. In general, the answer to 3x + 3y is 3 times the sum of x and y.
5x + 3y - 2 - x + y + 2 = 4x + 4y = 4(x + y)
x+3y=2 x= -5 y = 1
If you mean: -x+3y = 6 and x+3y = 18 then by substitution x = 6 and y = 4